CGAS is a micronucleophagy receptor for the clearance of micronuclei. Issue 12 (2nd December 2021) - Zhao, Mengmeng; Wang, Fei; Wu, Juehui; Cheng, Yuanna; Cao, Yajuan; Wu, Xiangyang; Ma, Mingtong; Tang, Fen; Liu, Zhi; Liu, Haipeng; Ge, Baoxue
ABSTRACT: Micronuclei are constantly considered as a marker of genome instability and very recently found to be a trigger of innate immune responses. An increased frequency of micronuclei is associated with many diseases, but the mechanism underlying the regulation of micronuclei homeostasis remains largely unknown. Here, we report that CGAS (cyclic GMP-AMP synthase), a known regulator of DNA sensing and DNA repair, reduces the abundance of micronuclei under genotoxic stress in an autophagy-dependent manner. CGAS accumulates in the autophagic machinery and directly interacts with MAP1LC3B/LC3B in a manner dependent upon its MAP1LC3-interacting region (LIR). Importantly, the interaction is essential for MAP1LC3 recruitment to micronuclei and subsequent clearance of micronuclei via autophagy (micronucleophagy) in response to genotoxic stress. Moreover, in contrast to its DNA sensing function to activate micronuclei-driven inflammation, CGAS-mediated micronucleophagy blunts the production of cyclic GMP-AMP (cGAMP) induced by genotoxic stress. We therefore conclude that CGAS is a receptor for the selective autophagic clearance of micronuclei and uncovered an unprecedented role of CGAS in micronuclei homeostasis to dampen innate immune surveillance. Abbreviations: ATG: autophagy-related; CGAS: cyclic GMP-AMP synthase; CQ: chloroquine; GABARAP: GABA type A receptor-associated protein; GFP: green fluorescent protein; LAMP1: lysosomal associated membrane protein 1; LAMP2: lysosomal associated membrane protein 2; LIR, MAP1LC3-interacting region; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; NDZ: nocodazole; STING1: stimulator of interferon response cGAMP interactor 1